(untitled) (Iranian Journal of Kidney Diseases, 2021)
Introduction. Steroid-dependent (SD)/frequently relapsing (FR) nephrotic syndrome (NS) follows a relapsing and remitting course. It is also characterized by proteinuria and edema, which can significantly affect health-related quality of life (HRQOL) in children. This study evaluated the effectiveness and safety of a single dose of rituximab (RTX) as well as the impact of RTX on HRQOL in children with SDFRNS. Methods. Sixteen children with SDFRNS were enrolled in the study. Each patient was administered a single intravenous dose of RTX (375 mg/m2). Effectiveness was defined as remission of proteinuria. The side effects of RTX were monitored. HRQOL was assessed using PedsQL™ 4.0 Generic Core Scales. Results. All the patients completed the study. Three SDNS patients and three FRNS patients discontinued treatment over 1 to 3.25 years of follow-up. Additionally, three SDNS patients and three FRNS patients experienced 1 to 2 relapses. The mean relapse-free period was 79.0 ± 77.6 days. The mean dosages of prednisolone and other immunosuppressants required were significantly lower (P < .05, < .001) six months after treatment with RTX compared with six months before treatment. Relapse rate was significantly reduced (P < .001) after treatment with RTX. Skin rash, hypotension, and fever were observed in one child. Total health score and physical, emotional, and school functioning were significantly higher six months after treatment with RTX (P < .001). Conclusion. A single dose of RTX is effective and safe for children with SDFRNS and can improve HRQOL, especially physical, emotional, and school functioning.